Chicory Aroma Water for Neonatal Jaundice: A Randomized Clinical Trial: - Pasalar, Mehdi; Manouchehrian, Mohsen; Shakiba, Mehrdad; Shariat, Mamak; Kamalinejad, Mohammad; Jafarian, Ali Akbar; Lotfi, Mohammad Hassan; Keighobady, Naeimeh (Galen Medical Journal, 2017)
Background: Although neonatal jaundice occurs in 60% of term infants, very little evidence is available on how to prevent it. Given the ethno-medical use of chicory aroma water (CAW) for the management of jaundice by Iranian pregnant women, the aim of this study was to evaluate whether the frequent CAW consumption was associated with fewer jaundice symptoms after 40 days. Materials and Methods: A single blind randomized controlled trial was designed to enroll participants from Lolagar Hospital, Tehran, Iran. Pregnant women (n=80) were randomly divided into two groups. The trial group was provided with common diet and an instruction to consume CAW. The control group was maintained on common diet. The proportion of phototherapy and mean value of bilirubin were measured and compared between the two groups. (IRCT registry number: IRCT2017041633475N1) Results: There was no statistically significant difference in the mean value of bilirubin between the women with frequent CAW consumption compared with the control. Also, the intake of CAW was not associated with a marked improvement in the need for phototherapy (P > 0.05). Conclusion: The findings of this study highlighted that the intake of CAW by pregnant women failed to ameliorate neonatal jaundice. [GMJ.2017;6(4):312-8] DOI: 10.22086/gmj.v6i4.973